Kompetensi Pustakawan dalam Promosi Perpustakaan Pada Media Sosial - Syifa Najiah; Indira Irawati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research intends to examine and synthesize data regarding the problems encountered when attempting to promote on library social media and the competency of librarians. The Systematic Literature Review (SLR) technique, which is being used for this descriptive research, has three stages: planning, implementation, and reporting. SLR is a thorough evaluation of studies that are pertinent to a topic that are then identified, evaluated, and synthesized methodically with the goal of eliminating bias in order to produce more trustworthy results. The examination of 23 publications that met the criteria revealed that ICT, communication, knowledge, attitude, information literacy, pedagogy, information analysis, management, and visual skills were the abilities most commonly identified to promote social media promotion. entrepreneurship, literacy, and digital literacy. Diverse information needs and behaviors, a lack of collaboration with other parties, the abundance of information sources, a failure to adapt to information search developments, a lack of staff, a lack of scientific publications that promote their work, a lack of format management skills and minimal collections, the emergence of online culture in the millennial generation, and the availability of a variety of social media platforms are all obstacles that librarians must overcome when promoting themselves on social media. The findings of this study can be used as a guide to examine trends in librarian abilities linked to social media promotion and as a basis for librarians to consider when deciding which competencies to develop for social media promotion.